Dr. Thomas Willis and his ‘Circle’ in the Brain - Rana, PVS (Nepal Journal of Neuroscience, 2005)
With the advances in microneurosurgery and the ability to tackle diseases of the intracranial arteries at the base of the brain (often referred to as the Circle of Willis) surgically more effectively, accurate knowledge of the intracranial vascular anatomy is increasingly important. Although Dr. Thomas Willis is best remembered for the accurate description of arterial anastomosis at the baseof the brain, his contribution to neuroanatomy, physiology and medical science in general is vast, and several diseases bear his name. In this article an attempt has been made to review the life of Dr. Willis followed by a short description of the “Circle of Willis.” Nepal Journal of Neuroscience, Volume 2, Number 1, 2005, Page: 77-79